A research of service quality perceptions and patient satisfaction: Case study of public hospitals in Romania. (17th November 2021) - Radu, Florin; Radu, Valentin; Turkeș, Mirela Cătălina; Ivan, Oana Raluca; Tăbîrcă, Alina Iuliana
Abstract: The quality of medical services provided by public hospitals has become a crucial principle in health. Awareness and satisfaction of patients are increasing in pace with technological processes and therapeutic procedures. Therefore, Romania's public hospitals must provide quality to patients and assure medical staff's efficiency and professionalism, a high level of satisfaction, and patient safety. This paper aimed to evaluate patient satisfaction measures used in Romania's Healthcare System. Between January and February 2019, an exploratory study was conducted. Data were collected through face‐to‐face interviews based on a questionnaire only with patients who used the health system last year. The results showed that only 39.71% of Romanians are satisfied with the quality of medical services, which means that 61.29% of respondents are disappointed by the health system. Because it is free of charge, the public sector is the only option available for a wide range of patients. The study's results may be an essential basis in developing and successfully improving marketing research on the quality of medical services provided through public hospitals especially considering that Romania must improve the health care system perception. Findings suggest that traditional patient satisfaction measures fail, and new ways must be taken into consideration. Key Points: The Romanian Health System was reformed after 2007, to ensure a high level of cohesion and social protection at the European level. Despite administrative differences and financial means, they are based on shared values recognized at the European level The most common obstacles to healthcare access were caused by patients' inability and/or reluctance to pay for medical products and services. In some countries, there was also the issue of waiting time Further specification and explicit criteria are needed to show that improving health care services should be a fundamental principle underpinning any action plan on increasing patient satisfaction The Romanian Health System must be changed or revigorated by attracting more medical staff, training more professionals, enhancing food and hospitality services, improving hygiene and cleanliness, and establishing new specialized sections/hospitals